Klippel-Trenaunay syndrome: a rare case not to be missed - Mohamed Shukor, Ahmad Zulkifli; Saiful Suhardi, Mohd Aiman; Abidin, Mohd Radhwan; Zainulabid, Ummu Afeera (Persatuan Saintis Muslim Malaysia, 2022)
Klippel-Trenaunay syndrome (KTS) is a rare congenital disorder characterised by malformation of capillary-venous vascular. In most reported cases, KTS was diagnosed clinically. However, this syndrome's clinical manifestations range from modest asymptomatic illness to life-threatening haemorrhage and embolism. Here we presented a case of a middle-aged woman who had experienced recurrent chronic thromboembolism events. She presented with middle cerebral artery infarction complicated with lower limb popliteal vein thrombosis. Subsequently, she was admitted to our centre and diagnosed with pulmonary embolism. The unilateral hypertrophic limb and cutaneous lesion over the right lower limb were mistakenly assumed as a birthmark. We reported this case due to its rare occurrence and to increase awareness of this condition.